2013
DOI: 10.1155/2013/652735
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nerve Growth Factor Signaling in Sensory Neurons of Early Diabetic Rats Is Corrected by Electroacupuncture

Abstract: Diabetic polyneuropathy (DPN), characterized by early hyperalgesia and increased nerve growth factor (NGF), evolves in late irreversible neuropathic symptoms with reduced NGF support to sensory neurons. Electroacupuncture (EA) modulates NGF in the peripheral nervous system, being effective for the treatment of DPN symptoms. We hypothesize that NGF plays an important pathogenic role in DPN development, while EA could be useful in the therapy of DPN by modulating NGF expression/activity. Diabetes was induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Thus, acupuncture can modify the expression of different genes and the expression of genes that control transcriptional factors that are crucial for cell homeostasis [60]. In Figure 1, we summarized the acupuncture mechanisms and mediators in CIPN based on what we know from animal studies of diabetic neuropathy [59, 61] and from human studies of brain imaging during acupuncture [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, acupuncture can modify the expression of different genes and the expression of genes that control transcriptional factors that are crucial for cell homeostasis [60]. In Figure 1, we summarized the acupuncture mechanisms and mediators in CIPN based on what we know from animal studies of diabetic neuropathy [59, 61] and from human studies of brain imaging during acupuncture [62]. …”
Section: Discussionmentioning
confidence: 99%
“…After this first examination, a seed of Vaccaria was applied on the top of the scaphoid fossa of one earlobe in the region corresponding to the finger-tips and finger-backs in Nogier's somatotopic map ( Figure 2 ; treated group) or on the neck (control group). Vaccaria seed was applied by Dr. Nori, a qualified and trained physician [ 16 , 32 ]. The acupoint was selected by searching the point most sensitive to a probe (tip tweezers) and tender to palpation.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Chan et al [ 29 ] found an increased concentration of the spinal antinociceptive neurotransmitter substance P in skin tissue samples derived from acupuncture points in anesthetized dogs, thus suggesting that there is a difference in the neurochemical profile between acupuncture points and control points. Concerning the molecular mechanisms involved in the nociceptive signaling pathways modulated by AT, it has been reported that AT by acupuncture-based techniques exerts its therapeutic effects causing a decrease in activity of the p38 signaling pathway in the spinal cord [ 30 ], an increase in NF- κ B activity [ 31 , 32 ], and a negative regulation of nerve growth factor (NGF) [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…** P<0.01, compared with the normal group; # P<0.05, ## P<0.01, compared with DNP group options are very limited and only marginally effective. EA has become increasingly popular and is used in the treatment of patients with chronic diseases of the nervous system, including DNP (Nori et al, 2013). EA has been demonstrated as a therapy for managing DNP safely and effectively (Nori et al, 2013), although its mechanism of action remains unclear.…”
Section: Effects Of Acupuncture At 2 or 100 Hz On Type 2 Dnpmentioning
confidence: 99%
“…EA has become increasingly popular and is used in the treatment of patients with chronic diseases of the nervous system, including DNP (Nori et al, 2013). EA has been demonstrated as a therapy for managing DNP safely and effectively (Nori et al, 2013), although its mechanism of action remains unclear. The analgesic effect produced by EA depends on proper prescription of specific acupoints and electrical parameters.…”
Section: Effects Of Acupuncture At 2 or 100 Hz On Type 2 Dnpmentioning
confidence: 99%